HUBUNGAN JARAK LOKASI PENANGKAPAN TERHADAP HASIL TANGKAPAN DAN DISTRIBUSI FREKWENSI UKURAN RAJUNGAN DI PERAIRAN KABUPATEN PANGKEP - Mustamin Tajuddin; Beddu Tang; Muhammad Saenong (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
The purpose of this study is to find out the distance relationship of the location of the gill net rajungan fishing gear to the catch of knitting (Portunus pelagicus). This study was conducted from September to November 2019 in the waters of Balang Lompo Island, Pangkep Regency, South Sulawesi Province. The study used field observation methods to conduct observations, measurements and data retrieval, covering primary and secondary data. Data processing uses the help of statistical data processing programs. Based on the results of research that the distance relationship of the location of the gill net rajungan fishing gear to the catch of rajungan (Portunus pelagicus) in the waters of Balang Lompo Island, is very crowded, the farther from the beach the greater the number of catches.